Functional Hypophysectomy Simply by Neck-Strangulation in the Rat: Applications for ACTH and LH Assays - Ryo Nakayama; Reiko Fujiwara; Michio Masuoka; Chiharu Higashiyama; Takashi Nonoyama (Elsevier, 2004)
The classical methods for hypophysectomy require a long training-period and at the end of each experiment, it is required to check any undue remnant of the hypophyseal tissue in the sella turcica, and there must be exclusion of such datum with the remnant from the experimental group. The present method for functional hypophysectomy by neck-strangulation in the rat is very simple to perform so that even an experimenter with little experience can become easily accustomed to the technique and obtain a number of functionally hypophysectomized preparations at any time he intends, with no need to check the remnant. The cerebral blood circulation of vertebrally dislocated rats was immediately intercepted by means of neck-strangulation and artificially respired. Fifteen minutes after intravenous injection of ACTH (0.1 - 3.2 mU/rat) or LH (312.5 - 2500 ng/rat), blood was sampled from the vena cava, and sera were examined for corticosterone or testosterone by radioimmunoassay. A linear dose-response relationship was obtained within a dose range of 0.2 - 1.6 mU/rat of ACTH and 312.5 - 1250 ng/rat of LH. In the ACTH assay, parapharyngeally hypophysectomized rats were compared. It was found that the sensitivity of functionally hypophysectomized preparations was 2.72 times higher than that of the parapharyngeally hypophysectomized rats. Keywords:: hypophysectomy, neck-strangulation, ACTH, LH